Embryonal origin of metanephric adenoma and its differential diagnosis - Sarlós, Donát Péter; Kovacs, Gyula (Anticancer research, 2018)
Background/Aim: The association of Wilms' tumor (WT), papillary renal cell tumor (PRCT) and mucinous tubular and spindle cell carcinoma (MTSCC) with embryonal rests has already been documented, but the cellular origin of metanephric adenoma (MA) is not yet known. The aim of this study was to understand their developmental evolution and find diagnostic markers. Materials and Methods: CD57, KRT7, AMACR, SCEL, WT1 and CDH17 expression was analysed by immunohistochemistry in the four types of tumors and the associated pre-neoplastic lesions. Results: Immunohistochemistry was able to differentiate WT, MA, MTSCC and PRCT. A phenotypic correlation between MA and perilobar nephrogenic rest associated with WT was identified. Conclusion: Perilobar nephrogenic rest and MA arise from differentiation arrested cells of the proximal domain of the S-shape body. We propose that WT1, MA, MTSCC and PRCT derive from different forms of maturation arrested embryonal rests.
Gesehen am 21.05.2019